Propagation of Short Pulses in Plasma Half-Space (Ionosphere) - Gutman, A.L. (Радиофизика и радиоастрономия, 2002)
The exact solution of the problem in the half-space of non-homogeneous plasma is obtained, and an asymptotic method for the same task as well. The estimations of the non-linearity and the electron-atom collisions influence regarding the problem are carried out.